Recording cortico-cortical evoked potentials of the human arcuate fasciculus under general anaesthesia. Issue 8 (August 2021) - Giampiccolo, D.; Parmigiani, S.; Basaldella, F.; Russo, S.; Pigorini, A.; Rosanova, M.; Cattaneo, L.; Sala, F.
Highlights: We show for the first time in adults that cortico-cortical evoked potentials (CCEPs) of the major language pathway, the arcuate fasciculus, are feasible also during surgery under full general anaesthesia. A novel P1 component at 12 ms together with an N1 component at 21 ms were identified. The N1 component may resemble the one described during awake procedures. CCEPs of the arcuate fasciculus are best identified stimulating from the middle temporal gyrus and recording from the ventral premotor cortex and inferior frontal gyrus. Abstract: Objective: We examined the feasibility of using cortico-cortical evoked potentials (CCEPs) to monitor the major cortical white matter tract involved in language, the arcuate fasciculus (AF), during surgery under general anaesthesia. Methods: We prospectively recruited nine patients undergoing surgery for lesions in the left peri-sylvian cortex, for whom awake surgery was not indicated. High angular resolution diffusion imaging (HARDI) tractography was used to localise frontal and temporal AF terminations, which guided intraoperative cortical strip placement. Results: CCEPs were successfully evoked in 5/9 patients, showing a positive potential (P1) at 12 ms and a negative component (N1) at 21 ms when stimulating from the frontal lobe and recording in the temporal lobe. CCEP responses peaked in the posterior middle temporal gyrus. No CCEPs were evoked when stimulating temporal sites and recording from frontal contacts. Conclusion: For the first time, we show that CCEPs can be evoked from the peri-sylvian cortices also in adult patients who are not candidates for awake procedures. Our results are akin to those described in the awake setting and suggest the recorded activity is conveyed by the arcuate fasciculus. Significance: This intraoperative approach may have promising implications in reducing deficits in patients that require surgery in language areas under general anesthesia.